The Effect Of Profitability and Firm Size On Firm Value With Capital Structure As a Mediating Variable In Companies Transportation Sub-Sector Companies Listed On The Indonesia Stock Exchange - Widyawati, Dewi; Lasmini, Rizki Sri (Financial Management Studies, 2023)
This study aims to analyze the effect of profitability and firm size on firm value with capital structure as a mediating variable. This research was conducted at 29 transportation sub-sector companies on the Indonesia Stock Exchange. The data used from 2016 to 2020. The data is obtained from the annual report published on the IDX website or the website of each transportation sub-sector company. The analysis method used is path analysis, where testing of direct effects is done through the t-statistic test, while testing of indirect effects is done using the Sobel test. The testing process was carried out using SPSS. This research is conducted by using two equation models. In the first equation, it is found that profitability has a positive and significant effect on capital structure, while company size has no significant effect on the capital structure of transportation sub-sector companies on the Indonesia Stock Exchange. In the second equation model, it is found that profitability has no significant effect on firm value, but company size and capital structure have a significant effect on firm value. At the stage of testing the indirect effect conducted with the Sobel test, it is found that the capital structure is able to mediate the relationship between profitability and firm value. In addition, from the results of the second indirect effect test, it is also found that the capital structure is able to mediate the relationship between company size and the company's capital structure.